POLITIK HUKUM PEMBERIAN ASIMILASI DI RUMAH BERDASARKAN PERMENKUMHAM NO. 10 TAHUN 2020 (Studi Kasus di Lapas Perempuan Kelas IIA Malang) - Elizabeth Nanik Khrisnawati (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2020)
The above theme taking is motivated by the policy of assimilation of prisoners in the midst of the COVID-19 pandemic, namely the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration for Prisoners and Children in the Framework of Prevention and Countermeasures of the Spread of COVID-19. Assimilation is granted as an inmate's right after fulfilling the conditions in the applicable law. Assimilation is the fostering of adult and child inmates by allowing them to live mingling in the community. The formulation of the issue raised is